The EARLY MARRIAGE FROM THE PERSPECTIVE OF ISLAMIC LAW AND ITS IMPACT - Aldisa, Nabila Zahwa (Program Studi Hukum Keluarga Islam UIM Pamekasan, 2025)
Early marriage is a social phenomenon that still occurs frequently, especially in communities with limited access to education and information. From the perspective of Islamic law, early marriage is permitted as long as it meets the requirements and harmony of marriage, but requires physical, mental and financial readiness. The negative impacts that arise from early marriage include anxiety, stress, depression, and social isolation. This research uses a literature analysis and case study approach to explore the views of Islamic law and the mental health impacts associated with early marriage. This article also proposes several solutions, such as religious education, psychosocial support, and policies that involve synergy between Islamic law and national regulations.